DAMPAK PENGGUNAAN EKONOMI DIGITAL TERHADAP BIAYA TENAGA KERJA PADA UMKM INDUSTRI BAKPIA DI KOTA YOGYAKARTA - Nur Widiastuti (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2022)
This study aims to analyze the use of the digital economy in the Bakpia MSME industry in Yogyakarta City and determine the effect of the digital economy, length of business, owner's last education, number of machines used, and age of business owner on labor wages paid by business owners. The method used is descriptive statistics and multiple regression analysis. The results showed that the digital economy run by the Bakpia MSME industry in Yogyakarta mostly used 2 to 3 gadgets, and internet costs were less than Rp. 200,000 per month, used 2 to 3 E-commerce and 2 to 3 social media. The digital economy does not affect the labor wages paid by business owners, the length of business and the level of education of business actors also do not affect the number of labor wages paid, while the number of machines used has a positive effect on the labor costs paid, while the age of the business owner has a negative effect. of labor costs paid.